عالقة دبلوماسية الطاقة بصنع القرار في السياسة الخارجية - Shalaw Abdulkhaliq Mohammed; Najdat Sabri Aqrawi (QALAAI ZANIST JOURNAL, 2019)
Nowadays ،among the foreign policy tools that can be used in external decision-making ،energy diplomacy is one the most important. This paper ، addresses the nature of the relationship between energy diplomacy and foreign policy decision-making process ،which is the central stage of the political process in all countries at the international level. In addition to that ، through this research ،we go beyond other recent studies on this subject ، linking the most important actors on the external side of energy policy with the most important features of foreign policy. Therefore ،we analyze factors that drive energy diplomacy to influence the foreign policy-making dynamics of both energy-exporting and importing countries. In conclusion ،the research has arrived at this fact that some countries succeeded in using energy as a weapon to implement foreign policy; however, in other cases ،a number of countries have failed to use it specifically as a hard power. Generally ، countries have worked to reach energy resources to use it for their decisionmaking process within the framework of energy diplomacy to reach their countries’ goals internationally.